PELATIHAN TEKNIK DASAR PERMAINAN TENIS - M. Sahib Saleh; Syahruddin Syahruddin; Muhammad Syahrul Saleh; Ilham Kamaruddin; Fahrizal Fahrizal (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2023)
Basic technique is one of the main components to achieve achievement. Therefore, tennis beginners or those who are new to tennis should learn/practice basic techniques in playing tennis. Furthermore, if novice tennis players have mastered these basic techniques, it will facilitate the learning process for more complex and varied stroke techniques. With minimal problems in playing tennis, especially beginners or those who are new to tennis in hitting basic techniques. This is a problem that must be found a solution in popularizing and looking for tennis seeds among students in South Sulawesi, especially in the city of Makassar. The method used in this implementation is a direct approach of demonstration, discussion, practice, and evaluation. The subject of this community service was 20 students of SMP Negeri 18 Makassar. Based on the results of the dedication that has been done, it can be concluded that the training in the basic techniques of playing tennis can run smoothly and the students of SMP Negeri 18 Makassar are able to demonstrate well by doing the basic techniques of forehand and backhand strokes.